Implication to performance and injury risks: the kinematics and kinetics involved in the execution of the drag flick between elite and sub-elite field hockey players - Aziz, L.; Lee, M. (ISBS Proceedings Archive (Michigan), 2018)
The main objective in field hockey is to score in order to win and the most efficient technique utilised to score is the drag flick. This study aimed to analyse the drag flick motion to better understand the kinematics and kinetics involved in attributing to performance and injury risks. One world class elite athlete and three sub-elites athletes were recruited in which they performed a series of drag flick shots. A 12-camera VICON MX camera and one Kistler force plate were used to determine the variables of interest. There was a reduction in pelvis range of motion and angular velocity from proximal-to-distal segments, and an increased internal rotation moments for the sub-elites compared to the elites. This is indicative of a lack of technique proficiency and increased risk of injury at the hip which can be improved by targeted training and strength and conditioning.